Environmental impact assessment, integrated development planning and the pursuit of sustainable development in South Africa : a critical reflection on the consideration of alternatives - Gerber, Gerhard (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2009.